HOUSING CRISIS IN ALGERIA: CHALLENGES AND PERSPECTIVES - Riadh, Djafri; Mohamed Osman, Mariana (PLANNING MALAYSIA, 2021)
The provision of good quality housing remains a major problem facing policymakers in developing countries, with Algeria being no exception. The Algerian policy focuses on ensuring the provision of housing to low-income households who cannot house themselves adequately. This article presents an overview of the Algerian housing policies focusing on the issues encountered by governments since independence in 1962. This entails presenting the history of Algerian housing policy, including colonial, after independence and new Algeria. This will not be completed without reviewing the different national housing plans and policies introduced by the Algerian government, focusing on the housing achievements and deficits. Using qualitative analysis of secondary data through narrative and inductive approaches, this research argues that a significant change in how these programmes are currently structured is urgent. Thus, there is a need to find a new approach to finance the construction of public and private housing units and reduce dependence on the Public Treasury.